Ennis Franciscan Friary, tomb niche under tower, jamb and arch - O'Donovan, Danielle (My University, 2008)
Sketch of jamb and arch, moulding comprises from intrados out: hollow chamfer, hollow chamfer, hollow chamfer, right-angled rebate, hollow chamfer, hollow chamfer. One of a number of Flamboyant tombs found on or west of the Shannon. The Ennis example is closest in design to that in the north chancel wall at Athenry Dominican Friary.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; moldings, hollow